What is the efficacy and safety of immediate postpartum initiation of longacting reversible contraceptives (LARCs) versus waiting until 6 weeks postpartum?. Issue 5 (May 2018) - Day, Margaret; Bruck, Madeline
Abstract : EVIDENCE‐BASED ANSWER : Intrauterine device (IUD) placement at the time of delivery compared with 4 to 12 weeks postpartum may have up to a 4‐fold higher risk of expulsion within 6 months. However, early placement also appears to increase IUD use for at least 6 months. No complications are reported with immediate insertion (SOR: A, meta‐analysis of RCTs and single RCT).